Increased Coastal Nutrient Loading Enhances Reproductive Intensity of Zostera marina: Implications for Seagrass Meadow Resilience - Suonan, Zhaxi; Kim, Seung Hyeon; Qin, Le-Zheng; Kim, Hyegwang; Zhang, Fei; Lee, Kun-Seop (Frontiers in Marine Science, 2022)
Because sexual reproduction is essential for the establishment and persistence of seagrass meadows, flowering intensity is an important trait that influences the resilience and stability of seagrass populations. Although the effects of excessive coastal nutrient loading on seagrass vegetative growth have been extensively documented, the effects on seagrass reproductive phenology and intensity remain unclear. To examine the reproductive responses of seagrass populations to increased coastal nutrient loading, the flowering phenology and intensity of Zostera marina were compared between sites with high-nutrient, low-light conditions (Deukryang Bay and Dongdae Bay) and low-nutrient, high-light conditions (Koje Bay) on the southern coast of Korea. Nutrient contents of the above- and below-ground tissues of Z. marina reflected in situ nutrient and light availability at the study sites. Reproductive shoot density and biomass, as well as flowering frequency and reproductive effort, were much higher (1.5–4.6-fold) at the high-nutrient, low-light study sites of Deukryang Bay and Dongdae Bay than at the low-nutrient, high-light site of Koje Bay. Consequently, potential seed production was higher in Deukryang Bay and Dongdae Bay than in Koje Bay. Chronic high-nutrient and low-light conditions significantly increased the reproductive intensity of Z. marina, supporting the persistence and resilience of Z. marina populations. The results of this study could provide insights into the conservation and management of seagrass meadows under increased coastal nutrient loading.